Direct Transfer Printing with Metal Oxide Layers for Fabricating Flexible Nanowire Devices. (15th October 2015) - Lee, Sang Hoon; Lee, Tae Il; Ham, Moon‐Ho; Lee, Su Jeong; Park, Ji Hyeon; Kim, Yun Cheol; Biswas, Pranab; Myoung, Jae Min
Abstract : A direct printing method for fabricating devices by using metal oxide transfer layers instead of conventional transfer media such as polydimethylsiloxane is presented. Metal oxides are not damaged by organic solvents; therefore, electrodes with gaps less than 2 μm can be defined on a metal oxide transfer layer through photolithography. In order to determine a suitable metal oxide for use as transfer layer, the surface energies of various metal oxides are measured, and Au layers deposited on these oxides are transferred onto polyvinylphenol (PVP). To verify the feasibility of our approach, Au source–drain electrodes on transfer layers and Si nanowires (NWs) addressed by the dielectrophoretic (DEP) alignment process are transferred onto rigid and flexible PVP‐coated substrates. Based on transfer test and DEP process, Al2 O3 is determined to be the best transfer layer. Finally, Si NWs field effect transistors (FETs) are fabricated on a rigid Si substrate and a flexible polyimide film. As the channel length decreases from 3.442 to 1.767 μm, the mobility of FET on the Si substrate increases from 127.61 ± 37.64 to 181.60 ± 23.73 cm 2 V −1 s −1 . Furthermore, the flexible Si NWs FETs fabricated through this process show enhanced electrical properties with an increasing number of bending cycles. Abstract : Flexible Si nanowire field effect transistors (FETs) are fabricated by a direct printing method applying an Al2 O3 layer. As metal oxide is not damaged by organic solvents, source–drain electrodes with less than 2 μm can be patterned by photolithography. Unlike typical flexible devices, the FETs produced through the proposed process exhibit enhanced electrical properties with an increasing number of bending cycles.